Airborne observations of the 1992 Arctic winter stratosphere by FTIR solar absorption spectroscopy - Toon, G. C.; Blavier, J.-F.; Solario, J. N.; Szeto, J. T. (1993)
The JPL MkIV interferometer, a Fourier Transform Infra-Red (FTIR) spectrometer designed specifically for atmospheric remote sensing, made measurements of the composition of the Arctic stratosphere in January, February and March 1992. These measurements were made from the NASA DC-8 aircraft as part of the AASE2 campaign. The data reveal that despite 5 to 6 km of subsidence inside the vortex, which more than doubled the vertically integrated column amounts (burdens) of HF and HNO3 with respect to outside the vortex, considerable losses of NO2, HCl and ClNO3 were evident by mid-January. Temporary freeze-out of HNO3 was observed only on one occasion, Jan. 19, and was accompanied by substantial reductions in HCl and ClNO3. During February and March, ClNO3 and NO2 amounts increased dramatically. HCl also recovered but at a much slower rate, so that by March ClNO3 was the major reservoir of inorganic chlorine, at times exceeding HCl by a factor 2.